Analysis and design of a digital class D power amplifier - Gan, Hoe Yee (2010)
Class D power amplifier has become more prevalent in consumer electronics due to its high power efficiency of more than 90%. Furthermore, in today’s increasing trend of digital processing, the use of a digital Class D power amplifier brings in additional benefits due to the elimination of the digital-to-analogue converter (DAC).